Sexual Harassment and Academic Engagement of Female Students in Higher Education Institutions in Nigeria - Adimora, Dorothy Ebere; Adimora, Jane-Frances Chinenye (European Scientific Journal, ESJ, 2026)
This study explored the impact of sexual harassment (SH) on the academic engagement of female students in Higher Education Institutions (HEIs) in Nigeria. The normalisation of gender-based violence (GBV), toxic academic masculinity, a culture of silence, and a lack of active leadership were identified as key features that encourage SH in higher education and may lead to academic disengagement among female students. A qualitative case study and in-depth interview approach were employed for data collection. Students’ narratives were organised for analysis of the findings. The thematic focus included: (a) SH experienced by female students, and (b) SH and academic engagement. The study revealed poor academic (cognitive, affective, and behavioural) engagement among students, which was adversely affected by SH. These included difficulties connecting with academic activities, difficulty completing assignments, problems with presentations, a reluctance to ask questions or participate in group discussions, a sense of disorientation and disturbance, fear, a loss of motivation, poor psychological feelings towards school learning, teachers and peers, and students’ inability to receive the needed assistance from the teacher to attain higher academic achievement. However, due to limited trust in the institution, the lengthy legal process, and fear of being blamed, accused, or stigmatised, legal action against the harassers was rarely pursued.